Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
•ɦà↭ƙĭềυ↭σαηɦ•
Xem chi tiết
feeeeeeeeeeeeeeeeeeeeeee...
15 tháng 10 2019 lúc 19:58

A= E387E4837

B = 883433

C = UỲUWFHQWURY48E3947

Nguyễn Thị Hiền Trang
Xem chi tiết
Thanh Tùng DZ
22 tháng 10 2017 lúc 8:58

\(\left(3-\frac{1}{4}+\frac{2}{3}\right)-\left(5+\frac{1}{3}-\frac{6}{5}\right)-\left(6-\frac{7}{4}+\frac{3}{2}\right)\)

\(=3-\frac{1}{4}+\frac{2}{3}-5-\frac{1}{3}+\frac{6}{5}-6+\frac{7}{4}-\frac{3}{2}\)

\(=\left(3-5-6\right)+\left(-\frac{1}{4}+\frac{7}{4}-\frac{3}{2}\right)+\left(\frac{2}{3}-\frac{1}{3}\right)+\frac{6}{5}\)

\(=-8+\frac{1}{3}+\frac{6}{5}\)

\(=-\frac{97}{15}\)

Nguyễn Ngô Minh Trí
22 tháng 10 2017 lúc 9:01

= 3 - 1/4 +2/3 - 5 - 1/3 + 6/5 - 6  + 7/4 - 3/2

= 2/3 . -3/2 . ( 3 + 5 + 6 ) . ( 2/3 + 1/3 ) . ( -1/4 - 7/4) 

= -1 . 14 . 1 . 6/4

= -14 . 1 . 6/4

= -14 . 6/4

= -84/4 = -21

Nguyễn Tiến Dũng
22 tháng 10 2017 lúc 9:03

\(\left(3-\frac{1}{4}+\frac{2}{3}\right)-\left(5+\frac{1}{3}-\frac{6}{5}\right)-\left(6-\frac{7}{4}+\frac{3}{2}\right)\)

\(=3+\frac{-1}{4}+\frac{2}{3}-5+\frac{-1}{3}+\frac{6}{5}-6+\frac{7}{4}+\frac{-3}{2}\)

\(=3+\frac{-1}{4}+\frac{2}{3}+-5+\frac{6}{5}+-\frac{1}{3}+-6+\frac{7}{4}+\frac{-3}{2}\)

\(=\left(3+-5+-6\right)+\left(-\frac{1}{4}+\frac{7}{4}\right)+\left(-\frac{1}{3}+\frac{2}{3}\right)+\frac{6}{5}+\frac{-3}{2}\)

\(=-8+\frac{3}{2}+\frac{1}{3}+\frac{6}{5}+\frac{-3}{2}\)

\(=\left(\frac{3}{2}+\frac{-3}{2}\right)+\left(\frac{6}{5}+\frac{1}{3}+-8\right)\)

\(=\frac{18}{15}+\frac{5}{15}+\frac{-120}{15}\)

\(=-\frac{97}{15}\)

Huỳnh Thị Thu Uyên
Xem chi tiết
tran thi quynh nhu
Xem chi tiết
tran thi quynh nhu
Xem chi tiết
★彡 A͛r͛a͛k͛i͛ S͛e͛i͛j͛u...
Xem chi tiết
Trần Hà Mi
Xem chi tiết
Đỗ Lê Mỹ Hạnh
4 tháng 1 2017 lúc 22:07

a) \(A=\left(1:\frac{1}{4}\right).4+25\left(1:\frac{16}{9}:\frac{125}{64}\right):\left(-\frac{27}{8}\right)\)

\(=4.4+25.\frac{36}{125}:\frac{-27}{8}\)

\(=16-\frac{32}{15}=\frac{240}{15}-\frac{32}{15}=\frac{208}{15}\)

Lê Diệu Linh
Xem chi tiết
Lê Quang Phúc
8 tháng 9 2017 lúc 18:11

a) \(2^3+3.\left(\frac{1}{2}\right)^0+\left[\left(-2\right)^2:\frac{1}{2}\right]\)

\(=8+3.1+4:\frac{1}{2}\)

\(=8+3+8=19\)

b)\(\frac{2^{15}.9^4}{6^6.8^3}=\frac{2^{15}.\left(3^2\right)^4}{\left(2.3\right)^6.\left(2^3\right)^3}=\frac{2^{15}.3^8}{2^6.3^6.2^9}\)\(=\frac{2^{15}.3^8}{2^{15}.3^6}=3^2=9\)

c) \(\left(1+\frac{2}{3}-\frac{1}{4}\right).\left(\frac{4}{5}-\frac{3}{4}\right)^2\)

\(=\frac{17}{12}.\frac{1}{400}=\frac{17}{4800}\)

d) \(\left(-\frac{10}{3}\right)^3.\left(\frac{-6}{5}\right)^4=-\frac{100}{27}.\frac{1296}{625}\)\(=\frac{-4.48}{1.25}=-\frac{192}{25}\)

Fenny
Xem chi tiết